Industrial Ethernet network interconnection technology and development - Yu Huiqun; Huang Yihai; Peng Daogang; Wang Yixue; Ma Tao (Dianzi Jishu Yingyong)
With the development of information technology, the coverage of industrial Ethernet is increasing, and the interconnection of industrial networks becomes the basis for the transformation of modern factories to intelligent and digital. Firstly, the paper expounds the development policy of industrial Internet in China, the current situation of the industrial network market and the types of industrial Ethernet protocols to analyze the current obstacles to the interconnection of industrial networks. Secondly, the paper explores new methods for new technologies to promote the interconnection of industrial Ethernet networks. Finally, the paper puts forward constructive suggestions according to the status of industrial Ethernet and industrial Internet to promote the application of industrial Ethernet and the development of industrial Internet.